Um drink de tradição e novidade: considerações sobre Rilke Shake de Angélica Freitas - Escute, João Paulo Vieira [UNESP]; Martha, Diana Junkes [UNESP] (My University, 2013)
Angélica Freitas is one of the most productive poets of her generation and has established herself as one of the most interesting voices in contemporary Brazilian poetry. In the wake of a tradition of modernity in which the invention and canon are amalgamated, Angelica’s poems stand out for their colloquial diction, marking the entry of the day-by-day in her texts. This article discusses aspects of the work of the poet, more specifically, some poems of Rilke Shake, book in which there is a clear dialogue with the canon established from a treatment that oscillates between laughter and irony.

Angélica Freitas é uma das poetas mais produtivas de sua geração e tem se afirmado como uma das vozes mais interessantes da poesia brasileira contemporânea. Na esteira de uma tradição da modernidade, em que a invenção e o cânone se amalgamam, os poemas de Angélica destacam-se pela dicção coloquial, marcando o ingresso do cotidiano nos textos. Este artigo discute aspectos da obra da poeta gaúcha, mais especificamente alguns poemas do livro Rilke Shake em que é patente o diálogo com o cânone, estabelecido a partir de um tratamento que oscila entre o riso e a ironia.
Tradition and innovation drink: considerations on Rilke Shake, by Angelica Freitas
Keywords: poesia brasileira; tradição; contemporaneidade; Angélica Freitas; Rilke Shake; tradition; contemporary; Angélica Freitas; Rilke Shake; brazilian poetry